A Technical Note on a Modified Subcrestal Buccal Flap Approach to All-on-Four: A Case Report - Giovanella, Fernando [UNESP]; Bezerra, Fabio [UNESP]; Soares, Michel A. Dantas; Oliveira, Guilherme; Ghiraldini, Bruna (Springer, 2024)
This case report describes a dual full-arch rehabilitation focusing on a modified buccal incision for installation of four implants for full-arch rehabilitation of an edentulous maxilla. A modified buccal incision was performed in the subcrestal buccal region to promote direct access to the periosteum without incising the muscles in the region. For the installation of anterior implants, an 8.5 mm implant was locked in the cortical bone of the alveolar ridge and in the cortical bone of the floor of the pyriform cavity. The drilling point of the posterior implants was defined using the anterior implants as a visual reference, and the entry point could be visually estimated from the topography of the palatal surface of the maxilla. After bone leveling, the drilling enlargement sequence was carried out using drills that allowed the installation of long implants (18 mm). Straight mini-abutments were installed in the anterior implants and angled at 30 degrees in the posterior implants. The flap was then perforated in the exact region where the mini-abutments were located. The buccal incision line was sutured with continuous 5-0 nylon suture. On the following day, aesthetic tests were carried out with teeth mounting. The patient presented minimal edema, and the lip motricity and smile width were completely preserved. The prosthesis was delivered five days after surgery. The suture was removed, and the prosthesis was installed while maintaining compression on the gingival tissue. The patient reported no pain during the prosthesis installation. The modified buccal flap enables implant placement for full-arch rehabilitation of an edentulous maxilla.
Keywords: osseointegration; full arch rehabilitation; dental implants; atriphic ridge; all on four